METODE PEMBELAJARAN PQ4R DALAM PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V DI BEKASI - Rikmasari, Rima; Lestari, Mega (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
The aim of this study is to determine the application of learning methods PQ4R (Preview, Question, Read, Reflect, Recite, Review) in reading comprehension ofÂ  the fifth grade students in Indonesian lesson at SDN Cibuntu 06 Bekasi. The results showed that there was an increasing students' reading comprehension ability in each cycle, the first cycle classical completeness of 67.64% with an average value of 80.17, in the second cycle classical completeness reached 76.47% with an average value of 80, 55 and in cycle III classical completeness increased to 94.11% with an average student score of 84.61. The study means that to improve students' reading comprehension skills in Indonesian subjects can be applied the methods PQ4R (Preview, Question, Read, Reflect, Recite, Review)